Heterogeneity of Lipid Metabolism and its Clinical and Immune Correlation in Lung Adenocarcinoma - Zhang, Xugang; Li, Weiqing; Liu, Taorui; Guo, Huiqin; Sun, Qianqian; Li, Baozhong (Current Medicinal Chemistry, 2024)
Introduction: The role of lipid metabolism in lung adenocarcinoma (LUAD) is not completely researched. Lipid metabolism reprogramming is a characteristic of malignancies and contributes to carcinogenesis and progression. The transcriptome and scRNA- seq data and clinical information were downloaded from the public databases. Methods: Lipid metabolism pathways were collected from the MSigDB database, and molecular subtypes were classified based on lipid metabolism features via consensus clustering. The bidirectional crosstalk between immune cells and malignant cells was analyzed. Differences in lipid metabolism at the single-cell level and their correlation with the tumor microenvironment (TME) were also studied. LUAD patients were classified into two subtypes, showing distinct mutation and lipid metabolism features based on lipid metabolism characteristics. Meanwhile, significant differences in the overall survival, clinical characteristics, and immune landscape were observed between the two subtypes. We also found that clust1 had higher oxidative stress status. There were 116 differentially expressed genes between the two subtypes, which were significantly associated with cell cycle progression. We identified 4001 immune cells, including 483 malignant cells and 3518 normal cells, and found active intercellular communication and significant differences in lipid metabolism characteristics between the malignant cells and normal cells. Furthermore, several lipid metabolism pathways were found to be associated with TME factors, including hypoxia and angiogenesis. Result: The current findings indicated that lipid metabolism was involved in the development and cellular heterogeneity of LUAD and revealed widespread reprogramming across multiple cellular elements in the TME of LUAD. Conclusion: This characterization improved the current understanding of tumor biology and enabled the identification of novel targets for immunotherapy
Keywords: oxidative stress